A simple capillary-based open microfluidic device for size on-demand high-throughput droplet/bubble/microcapsule generation. Issue 18 (16th August 2018) - Mei, Liping; Jin, Mingliang; Xie, Shuting; Yan, Zhibin; Wang, Xin; Zhou, Guofu; van den Berg, Albert; Shui, Lingling
Abstract : A capillary-based open microfluidic device was established for flexible and controllable creation of monodisperse droplets of various fluidic materials. Abstract : We report an easily-established capillary-based open microfluidic device (COMD) as a simple and robust method for size on-demand generation of monodisperse droplets of various fluidic materials with controllable volume. A device is set up in which a capillary is positioned with its tip close to a flat surface with a precise gap distance in a container. The continuous phase remains static in the container, and the dispersed phase is pumped through the capillary and forms droplets at the exit of the gap. Monodisperse droplets, bubbles and microcapsules of various fluids with diameters of 10–300 μm (picoliter to nanoliter) and generation frequency of 1–1000 Hz are obtained by controlling the gap distance in the range of 5–500 μm. The droplet formation is caused by capillarity-induced narrowing of the dispersed phase at the capillary exit, with droplet size being determined by the gap volume and fluid flow. We find that, at low flow rate, using the same COMD, the generated droplet size is constant, being determined by the gap size; however, at higher flow rate, droplet size increases with the flow rate. Droplet types can be managed by fluids and surface modification of the capillary and bottom surfaces. High throughput droplet generation is achieved by in-parallel integration of multiple capillaries in one device. Such a COMD is simple and easy-to-build without complex microfabrication requirements; however, it is highly robust, flexible and easy-to-operate for size on-demand droplet generation. It offers an opportunity for common laboratories to perform droplet-based assays, and has high potential for high throughput industrial emulsification applications as well.